Dilemma for the Surgeon-A Three-part Broken Interlocking Femoral Nail: Novel Technique of Removal - Raviraj, A.; Sugumar, K. Abhishek; Maalepati, Vidyasagar; Shivareddy, H. A.; Anand, Ashish (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
A segmentally broken (three part) interlocking femoral nail with broken interlocking screw can be challenging to remove. We describe a novel technique for extraction of an unusual two level broken cannulated anterograde femoral nail to treat the delayed union with exchange nailing. This is the first reported case of a three-part broken intramedullary interlocking nail with broken distal locking screws, where the broken hardware was removed without opening the facture site or the knee. This technique is simple and does not require specialized equipment. We used a higher diameter and a longer nail for fixing the fracture and achieving the union. The surgical technique and review of literature is presented.